2016
DOI: 10.15585/mmwr.mm6527a1
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Product Use Among Adults — United States, 2013–2014

Abstract: of tobacco products, are critical to reducing tobacco-related diseases and deaths in the United States. § NATS is a stratified, random-digit-dialed landline and cellular telephone survey of noninstitutionalized U.S. adults aged ≥18 years. The 2013-2014 NATS included 75,233 respondents (70% landline, 30% cellular); the overall response rate was 36.1% (landline 47.6%, cellular 17.1%). Based on established conventions regarding patterns of tobacco product use (3), NATS questions used varying thresholds of lifet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
235
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(253 citation statements)
references
References 7 publications
17
235
0
1
Order By: Relevance
“…According to a research conducted in Russia, it was found that 15.8% of individuals who smoked on a regular basis were in the age group of 1518 years and 41.4% were in the age group of 19-24 years (23). In the United States, for the age group of 15-18 years, the percentage of individuals who consumed any tobacco product was 24.5%, where as that of individuals who smoked cigarettes was 17.0% (24). In Iran, the rate of smoking was 0.3% for the age group of 15-19 years and 4.8% for the age group of 20-24 years (25).…”
Section: Discussionmentioning
confidence: 99%
“…According to a research conducted in Russia, it was found that 15.8% of individuals who smoked on a regular basis were in the age group of 1518 years and 41.4% were in the age group of 19-24 years (23). In the United States, for the age group of 15-18 years, the percentage of individuals who consumed any tobacco product was 24.5%, where as that of individuals who smoked cigarettes was 17.0% (24). In Iran, the rate of smoking was 0.3% for the age group of 15-19 years and 4.8% for the age group of 20-24 years (25).…”
Section: Discussionmentioning
confidence: 99%
“…Among young adults ages 18-24 years, the combined prevalence of regular and intermittent (i.e. every day, some days, or rarely) WTS in 2013-2014 was 20.2% 1 . As a consequence, many young adults may face health risks due to WTS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study found current (30-day) use of electronic cigarettes among survey participants was 9.6%. While there are no available data for 30-day electronic cigarette use among N.C. adults, the most recent national data show a much lower rate of adult current electronic cigarette use (3.3%) 17 . Additional data are needed on all aspects of the use of these new products, including use among restaurant/ bar employees and patrons.…”
Section: Implications For Researchmentioning
confidence: 97%
“…The questions on the two pencil and paper surveys (Appendix A, supplemental file) were divided into four sections: "Questions about the current law" (questions 1-6), "Questions about electronic cigarettes" (questions 7-11), "Questions about outside seating areas" (questions [12][13][14] and "Additional questions" (questions [15][16][17][18][19][20], including a final open-ended question. Questions two through five were drawn from a telephone survey conducted by Linnan et al 10 .…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation